The Role of Psychological Factors In Career Choice and The Development of Abilities In Schoolchildren - Nurullayev Firuz Fayzilloyevich (Indonesian Journal Publisher, 2025)
This article explores psychological factors influencing schoolchildren's career choices and ability development. The study aims to identify how motivation, personal traits, and social context shape students’ professional orientation. Using a qualitative analytical method, the research draws from psychological and pedagogical literature, incorporating comparative and theoretical analysis. Results show that self-awareness, family influence, and social stereotypes significantly affect students’ career decisions, highlighting the need for integrated career guidance approaches involving schools, families, and society.